The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1348-0421.1992.tb02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6

Abstract: 551 552K. YAMANISHI balloon-like cells could be observed. When the cells were fixed and stained with the sera of acute and convalescent phase of ES, positive staining was observed only with the convalescent sera. Next, the cultured cells were observed by electron microscopy (EM) as reported elsewhere (74). The typical herpesvirus particles were found in the nucleus and cytoplasm of the cultured cells. Thus, the diameter of virion was 90-110 nm in the nucleus and 150-170 nm in the cytoplasm (91, 95), suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…It has also been established that reactivation of HHV-6 causes various clinical manifestations, including lymphadenitis, pneumonitis, hepatitis, meningoencephalitis, infectious mononucleosis-like disease, hemophagocytic syndrome, and hypersensitivity syndrome (3)(4)(5)(6). HHV-6 isolates are divided into two subgroups, HHV-6A and HHV-6B, on the basis of their tropism for certain cell lines, reactivities with mAbs and HHV-6-specific T lymphocyte clones, and restriction enzyme cleavage patterns (7)(8)(9).…”
Section: H Uman Herpesvirus (Hhv)mentioning
confidence: 99%
“…It has also been established that reactivation of HHV-6 causes various clinical manifestations, including lymphadenitis, pneumonitis, hepatitis, meningoencephalitis, infectious mononucleosis-like disease, hemophagocytic syndrome, and hypersensitivity syndrome (3)(4)(5)(6). HHV-6 isolates are divided into two subgroups, HHV-6A and HHV-6B, on the basis of their tropism for certain cell lines, reactivities with mAbs and HHV-6-specific T lymphocyte clones, and restriction enzyme cleavage patterns (7)(8)(9).…”
Section: H Uman Herpesvirus (Hhv)mentioning
confidence: 99%
“…ES is a common disease of infants or young children characterized by 3-4 days of high fever, followed by skin rash (11,20,21). Restriction enzyme analyses of DNAs of isolates obtained from peripheral blood of ES patients showed that these viruses were HHV-6B variants, similar to the Z29 prototype strain (6).…”
mentioning
confidence: 99%
“…Restriction enzyme analyses of DNAs of isolates obtained from peripheral blood of ES patients showed that these viruses were HHV-6B variants, similar to the Z29 prototype strain (6). In some cases ES is accompanied by a wide range of clinical complications from meningoencephalitis to fatal fulminant hepatitis (11,20,22,23). It was suggested that HHV-7 also causes ES, although in many of these cases the observed ES was associated with a large increase of HHV-6 antibody titers (16,19,24,25).…”
mentioning
confidence: 99%
“…Subsequent studies have revealed that HHV-6 is a causative agent of exanthem subitum in infants at primary infection (45). Reactivation of HHV-6 occurs frequently in patients who are immune deficient, such as organ transplant recipients and those with AIDS (24), and causes various disorders, including lymphadenitis, pneumonitis, hepatitis, meningoencephalitis, retinitis, infectious mononucleosis-like disease, hemophagocytic syndrome, and hypersensitivity syndrome (2,6,41,42,44). HHV-6 isolates are divided into two subgroups, HHV-6A and HHV-6B, on the basis of their tropism for certain cell lines, their reactivities with monoclonal antibodies (MAbs) and HHV-6-specific T-lymphocyte clones, and their restriction enzyme cleavage patterns (11,38,50).…”
mentioning
confidence: 99%